1982
DOI: 10.1007/bf00580477
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the accumulation of the alkaloids ofNitraria sibirica

Abstract: We have studied the total alkaloids present in various organs of Nitr~ga sibirica Pall. as functions of the vegetation period. Attempts were first made to determine the optimum method of extraction, as previously for N. komarovii [i]: the same amounts of samples of the comminuted plant were extracted in parallel by three methods: i) with a 2% solution of acetic acid in chloroform; 2) with methanol; and 3) with chloroform after the plant had been wetted with an 8% solution of ammonia.The purest combined materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…identified in plants of the Nitraria genus were initially isolated in these studies. These studies also observed that the content of alkaloids in the leaves is higher than the content in the roots, stems and seeds of Nitraria komarovii and Nitraria sibirica (37)(38). There are also various types of alkaloids that have been isolated and purified in other studies.…”
Section: Phytochemical Studiesmentioning
confidence: 87%
“…identified in plants of the Nitraria genus were initially isolated in these studies. These studies also observed that the content of alkaloids in the leaves is higher than the content in the roots, stems and seeds of Nitraria komarovii and Nitraria sibirica (37)(38). There are also various types of alkaloids that have been isolated and purified in other studies.…”
Section: Phytochemical Studiesmentioning
confidence: 87%
“…An interesting study was published in 1977 relating the Polybuffer Ò separation of alkaloids with an adaptation of the historical Craig apparatus. 4 Several publications have also studied the total amount of alkaloids in different plant organs of three Nitraria species (N. komarovii, 5 N. sibirica, 6 and N. schoberi 7 ), and according to the location. The most common species (N. schoberi) is the richest in alkaloids, both in the quantitative and (as we will show) qualitative respects; usually, the leaves contain the highest quantities of alkaloids.…”
mentioning
confidence: 99%